Potential of Halophilic Bacteria from Hypersaline Waters to Reduce Polyethylene Microplastic Abundance in Artemia sp. Culture: A Preliminary Indication of Degradation Based on Gravimetric Weight Loss - Nanda Wahyuni Al Humaero; Sadikin Amir; Bagus Dwi Hari Setyono (Study Program of Aquaculture, Department of Fisheries and Marine Science, Faculty of Agriculture, University of Mataram, 2026)
Polyethylene (PE) microplastic contamination in aquaculture systems can increase plastic particle exposure in zooplankton, including Artemia sp., while also elevating the risk of biological disturbance in cultured organisms. This study evaluated the potential of halophilic bacteria isolated from hypersaline waters to reduce PE microplastic abundance in Artemia sp. and to provide a preliminary indication of PE degradation based on gravimetric weight loss. A completely randomized design with six treatments and three replications was applied: P0 (without microplastics and bacteria), KN (PE 2 mg/L), KP (bacteria 106 CFU/mL), P1 (PE 2 mg/L + bacteria 106 CFU/mL), P2 (PE 2 mg/L + bacteria 107 CFU/mL), and P3 (PE 2 mg/L + bacteria 108 CFU/mL). The primary response variables were microplastic abundance in Artemia sp. and PE degradation efficiency, whereas growth, survival, and water quality were treated as supporting variables. The treatments significantly affected microplastic abundance in Artemia sp. KN produced the highest abundance (0.1100 particles/individual), whereas bacterial addition reduced the value to 0.0267 particles/individual in P1, 0.0267 in P2, and 0.0467 in P3. PE weight loss ranged from 20.0% to 31.1%, with the highest value recorded in P1. These findings suggest that a halophilic bacterial inoculum of 106 CFU/mL was the most promising level for early-stage PE bioremediation in Artemia culture systems. Nevertheless, because degradation was assessed only by gravimetric loss, the result should be interpreted as a preliminary indication and still requires abiotic controls, SEM, and FTIR confirmation.